Dragon goes house-hunting. Volume 4 - Tanuki, Kawo; Campbell, T (Seven Seas Entertainment, LLC, 2019)
The red dragon Letty has spent months traveling around with Dearia, a kindly elf with the fearsome title of Demon Lord. But just how did Dearia wind up as both an architect and the Lord of Darkness? It's time for the full tale of his past to come to light: the house-hunting adventures of a young elf and a mighty black dragon! -- from publisher.